Stress Analysis Of Aboveground Atmospheric Storage Tank Due To Edge Settlement - Norhafiza Binti Mohd Zukepeli, Norhafiza (Universiti Teknologi Petronas, 2010)
Aboveground atmospheric storage tank is one of the important equipment in plant operation. One of the possible failures which normally overlooked is the failure of the tank due to settlement. The objective of this project is to conduct a deformation analysis based on bending moment theory and finite element analysis on deformation and bending moment distribution along section of bottom plate of aboveground storage tank that might occur during edge settlement. The results that represented the effect of edge settlement amplitude, plate thickness and foundation stiffness coefficient was generated. Using the used model, the prediction of relationship between settlement, foundation stiffness and plate thickness can be developed and future prevention of tank settlement may be applied. Comparison of the result with the API Standard 653 shows that the API Standard 653 which does not take into account of the effect of tank plate thickness, foundation stiffness, plate shell junction stiffness gives in general a conservative estimation of the allowable edge settlement limit. Using the model, for 7.5mm bottom plate thickness and 1m radial length the settlement limit is equals to 36mm which is about 20% more than the limit set by API Standard 653 for the same thickness and radial length which is 30.8mm.